2008
DOI: 10.1038/gene.2008.63
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of FAS are regulated through an evolutionary conserved element in intron 2, which modulates cystic fibrosis disease severity

Abstract: We have analyzed frequent naturally occurring variants in the autogene FAS in two independent cystic fibrosis (CF) patient populations. Analysis of FAS expression levels from intestinal epithelial biopsies from 16 unrelated F508del-CFTR homozygotes showed a correlation between FAS intron 2 SNP rs7901656 and signals for Affymetrix GeneChip U133 Plus 2.0 probeset 204781_s_at consistent with a dominant model (P ¼ 0.0009). Genotype and haplotype analysis at six informative SNPs spanning the FAS gene locus was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…At present, it is unknown how apoptosis regulates the local defense to the pathogen, but it has been speculated that apoptotic cells downmodulate the inflammation and prevent an overshooting response. It is very interesting to note that recent studies by Kumar and colleagues with two independent cohorts of cystic fibrosis patients have demonstrated that allelic variants within intron 2 of the CD95 gene modulate the manifestation of cystic fibrosis [67]. This finding suggested that CD95-mediated signalling or apoptosis plays a role in P. aeruginosa infections in cystic fibrosis patients.…”
Section: Bacterial Infections and Ceramidementioning
confidence: 89%
“…At present, it is unknown how apoptosis regulates the local defense to the pathogen, but it has been speculated that apoptotic cells downmodulate the inflammation and prevent an overshooting response. It is very interesting to note that recent studies by Kumar and colleagues with two independent cohorts of cystic fibrosis patients have demonstrated that allelic variants within intron 2 of the CD95 gene modulate the manifestation of cystic fibrosis [67]. This finding suggested that CD95-mediated signalling or apoptosis plays a role in P. aeruginosa infections in cystic fibrosis patients.…”
Section: Bacterial Infections and Ceramidementioning
confidence: 89%
“…Studies from Kumar et al . on two independent CF patient cohorts demonstrate that allelic variants within intron 2 of the CD95 gene modulate the manifestation of CF disease further suggesting a role of CD95-mediated signalling/ apoptosis in cystic fibrosis [21]. …”
Section: Inflammation In Cystic Fibrosismentioning
confidence: 99%
“…The candidate genes STAT3, IL1B and IFNGR1 were extracted from the transcriptome data generated from the intestinal epithelium of F508del-CFTR homozygotes and non-CF controls. 26,32 STAT3 was observed to be upregulated in F508del-CFTR homozygous patients who do not exhibit residual chloride conductance based on transcriptome data from rectal suction biopsies from four F508del-CFTR homozygous patients without residual function, and three F508del-CFTR homozygous patients with median residual function and five F508del-CFTR homozygous patients with high CFTR-mediated residual function. IL1B and IFNGR1 were upregulated in CF as compared with non-CF control individuals based on the comparison of transcriptome data from 14 F508del-CFTR homozygous CF vs 8 non-CF rectal epithelial tissue samples.…”
Section: Study Populationmentioning
confidence: 99%
“…Consequently, several studied candidate genes were derived from the field of immunity, immunology and host defense such as the cytokines IL8, [24][25][26] IL1B 25,26 and TGFB1. [28][29][30] We report our data on three candidate genes as modifiers of CF investigated in the framework of the European CF Twin and Sibling Study, 26 based on which we have described previously the immunorelevant receptors for TNFa 31 and FAS 32 as CF modifiers. For this work, the signal transducer and activator of translation 3 (STAT3), the cytokine interleukin 1b (IL1B) and the receptor for interferon g (IFNGR1) have been selected based on transcriptome data comparing F508del-CFTR homozygous CF patients stratified for low, medium or high residual chloride secretion and non-CF controls.…”
Section: Introductionmentioning
confidence: 99%